2014 IEEE International Conference on Semiconductor Electronics (ICSE2014) 2014
DOI: 10.1109/smelec.2014.6920881
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of undoped polysilicon nanowire for pH sensor

Abstract: Polysilicon has great benefit in application of pH sensor due to the unique properties and easiness to use top-down approach. In this paper, we present fabrication and characterization of undoped polysilicon nanowire (NW) for pH sensor application. The fabrication processes steps involve were photolithography, etching, deposition and oxidation. 3-aminopropyltriethoxysilane or APTES were used to enhance the sensitivity of polysilicon layer as well as able to provide surface modification by undergoing protonatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…These available sites have the capability to either accept hydrogen ions by adsorption mechanism or release them in a dynamic exchange process according to the description of the binding site model. 20 The pH response is determined by the interaction of the surface silanol (SiOH) group produced from the hydrolysis of SiO 2 2,21 with the H + ions. This interaction can be briefly explained by two main processes, namely protonation (addition of cations) and deprotonation (removal of cations).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These available sites have the capability to either accept hydrogen ions by adsorption mechanism or release them in a dynamic exchange process according to the description of the binding site model. 20 The pH response is determined by the interaction of the surface silanol (SiOH) group produced from the hydrolysis of SiO 2 2,21 with the H + ions. This interaction can be briefly explained by two main processes, namely protonation (addition of cations) and deprotonation (removal of cations).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the fabrication and characterization of undoped polysilicon nanowire as a pH sensor was reported. 2 The work demonstrated that variation in pH from pH 2 to pH 12 results in the reduction of current by 1.2 times due to the higher concentration of OHand deprotonation of SiOH groups. Similar work was done by the same group of researchers on doped polysilicon nanowire as a biosensor showing opposite trends in current of the undoped nanowire for the same ranges of pH.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations